Morphological description of the lingual surface of Platyrrhinus infuscus under scanning electron microscopy (SEM) - Becerra Diaz , Paula Andrea; Bravo García, Carlos Alberto; Rodríguez Bolaños , Abelardo; Rodríguez Saza, Freddy (Therya Notes, 2026)
Lingual morphology in bats represents a key structure linked to their feeding habits, although it remains poorly explored in several Neotropical species. This study describes the tongue surface of Platyrrhinus infuscus using Scanning Electron Microscopy (SEM). Tissue from a specimen deposited in the collection of the Museo de Historia Natural de la Universidad Distrital Francisco José de Caldas (MHNUD) was analyzed. The papillae were classified according to the general categories described in the literature: circumvallate, fungiform, conical, and filiform. Eleven types of papillae were identified: circumvallate; fungiform with triangular, circular, and cusp-shaped morphologies; conical; filiform; giant tricuspid and bicuspid; horny; strictly filiform; digitiform; and bifid. Papillae in the root region showed lateral orientation, while those at the apex were directed toward the medial region of the tongue. The topographic arrangement of the papillae reflects the food trajectory: structures at the apex facilitate the fixation of fleshy fruits during flight, whereas keratinized papillae promote retention and swallowing. The posterior zone, dominated by circumvallate and fungiform papillae, appears to be associated with enhanced sensory perception. The observed patterns reinforce the association of P. infuscus with a frugivorous and insectivorous diet, providing functional evidence of interest for ecological and taxonomic studies of Neotropical bats.